A Savlon’s report analyzing the effect of promotional strategies on consumer purchasing behaviour - Ahmed, Tamjid (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.